Motivación en el aprendizaje de lenguas: estado de la cuestión - Zenotz Iragi, María Victoria (Huarte de San Juan. Filología y Didáctica de la Lengua, 2012)
This article reviews the different approaches which have been taken in motivation research in language learning from mid last century till nowadays. We focus first on a social-psychological approach, then on a cognitive approach and finally we present more modern perspectives which consider motivation as something qualitatively specific from every language learner.